Social and economic sustainability of multiple-use marine protected areas in Spain: A mixed methods, multi-scale study. (1st April 2019) - Rodríguez-Rodríguez, David; Merkohasanaj, Matilda; López, Iván
Abstract: Social perception is key to the success of biodiversity conservation policies. A range of socioeconomic guilds can be affected by marine conservation. Among them, fishers are the ones most likely affected and affecting marine protected areas (MPAs). Here, we assessed the perceptions on the sustainability of a type of multiple-use MPA, Fishing Reserves (FRs), by a broad spectrum of national (n = 16) and local (n = 14) stakeholder organisations pertaining to six socioeconomic sectors via two online surveys in Spain. We compared organisational perception by stakeholder organisations, and specifically by the fishing guild, with official fishing statistics for six FRs between 1998 and 2016 using a Before-After-Impact (BAI) research design. Spanish FRs were regarded as sustainable marine management tools by most marine and coastal stakeholders, with environmental effects perceived to be more positive than social and economic ones, respectively. However, primary sector organisations stated null or negative effect of FR designation on their activities, although official statistics showed a moderate to large increase in a number of professional fishing-related variables, including number of boats and crews, after designation of most FRs. Spatial scale did not affect stakeholder perception of local socioeconomic effects of FRs, although some relevant local socioeconomic variables that were thought to vary most after FR designation differed across scales. Some suggested managerial improvements for increased socioeconomic sustainability of Spanish FRs by the professional fishing guild included: greater stakeholder engagement in FR designation and operation, more flexible fishing regulations and stricter control of recreational fishing. Highlights: Spanish Fishing Reserves (FRs) were considered sustainable marine management tools. A sustainability gradient was perceived: environmental > social > economic. Primary sector organisations perceived negative or null effects of FR designation. Official statistics showed positive socioeconomic values of fishing in most FRs. Perception of local socioeconomic effects did not differ across spatial scales.